Pemberdayaan Masyarakat Melalui Pelatihan Pemanfaatan Limbah Ternak Menjadi Kompos Untuk Mewujudkan Ekonomi Hijau di Desa Kesik - Silma Maosuli; Sahraeni Sahraeni; Usnul Khotimah; M. Qusay Gis; Dea Dina Mutia; Rajisman Rajisman; Hanifah Dewina Azmi; Eva Yuniza; Majda Rumi; Ridho Apripamilo; Eduardus Bayo Sili (Indonesian Publication Center, 2026)
Livestock activities in rural areas generate large amounts of animal waste that may cause environmental pollution if not properly managed. In Kesik Village, Masbagik Subdistrict, East Lombok Regency, livestock waste is often left accumulated around barns, causing unpleasant odors and potential soil and water contamination. This community service activity aimed to improve community knowledge and skills in utilizing livestock waste as compost to support the green economy concept at the village level. The program was conducted using an educative and participatory approach through counseling and hands-on composting practices in Punik Agung and Tengak Timuk hamlets. The results showed increased community awareness of the environmental impacts of livestock waste and improved technical skills in composting. The utilization of livestock waste as compost contributed to environmental improvement and soil fertility, as well as added economic value through the potential use and marketing of compost products.